Effects of 12 weeks of functional and resistance training on stress perception and sleep quality in Bra-zilian older people - Eduardo Silva; Natália Bernardi; Marilene Marques; Samuel Morais; José Roberto Nascimento Júnior; Braulio Henrique Branco; Daniel Vicentini de Oliveira (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The study investigated the effects of a 12-week functional and resistance training program on the perception of stress and sleep quality in Brazilian older people, involving 49 participants. The Perceived Stress in older adults and the Pittsburgh Sleep Quality Index (PSQI) was used. The training protocol included a general warm-up, resistance and functional training sessions, followed by a cool-down phase, held twice a week, lasting an average of 60 minutes over the 12 weeks. Data analysis was performed using the Kolmogorov-Smirnov test, bootstrapping, t-tests and Pearson correlation, with a significance level of p < 0.05. The results showed a significant reduction in sleep disturbance and total sleep quality score after the intervention. Men initially had lower stress and better sleep quality in some aspects compared to women, while older people between 60 and 69 years old had improvements in sleep quality in certain aspects before and after the intervention, compared to older people aged 70 and over. Furthermore, a positive correlation was observed between the perception of stress and several components of sleep quality, such as subjective quality, duration and total score. In short, the study demonstrated that the exercise program had varying impacts on sleep quality, but not on the perception of stress among the older people, highlighting a significant improvement in sleep quality after the intervention.